Medical adjuvant treatment to increase patency of arteriovenous fistulae and grafts - Tanner, Nicola C (Cochrane Database Syst Rev, 2015)
BACKGROUND: End‐stage renal disease (ESRD) patients often require either the formation of an arteriovenous (AV) fistula or an AV interposition prosthetic shunt for haemodialysis. These access sites should ideally have a long life and a low rate of complications (for example thrombosis, infection, stenosis, aneurysm formation and distal limb ischaemia). Although some of the complications may be unavoidable, any adjuvant technique or medical treatment aimed at decreasing complications would be welcome. This is the second update of the review first published in 2004. OBJECTIVES: To assess the effects of adjuvant drug treatment in ESRD patients on haemodialysis via autologous AV fistulae or prosthetic interposition AV shunts. SEARCH METHODS: For this update the Cochrane Peripheral Vascular Diseases Group Trials Search Co‐ordinator searched the Specialised Register (last searched March 2015) and CENTRAL (2015, Issue 2). SELECTION CRITERIA: Randomised controlled trials (RCTs) of active drug versus placebo in people with ESRD undergoing haemodialysis via an AV fistula or prosthetic interposition AV graft. DATA COLLECTION AND ANALYSIS: For this update, the two review authors (NCT, ADS) independently assessed trial quality and one review author (NCT) extracted data. Information on adverse events was collected from the trials. The primary outcome was the long‐term fistula or graft patency rate. Secondary outcomes included duration of hospital stay, complications and number of related surgical interventions. MAIN RESULTS: For this update, an additional six studies were deemed suitable for inclusion, making a total of 15 trials with 2230 participants. Overall the quality of the evidence was low due to short follow‐up periods, heterogeneity between trials and moderate methodological quality of the studies due to incomplete reporting. Medical adjuvant treatments used in the trials were aspirin, ticlopidine, dipyridamole, dipyridamole plus aspirin, warfarin, fish oil, clopidogrel, sulphinpyrazone, and human type I pancreatic elastase (PRT‐201). Where possible, the included studies were pooled into similar medical adjuvant groups for meta‐analyses. All included studies reported on graft patency by measuring graft thrombosis. There was insufficient evidence to determine if there was a difference in graft patency in studies comparing aspirin versus placebo (three RCTs, 175 participants) (odds ratio (OR) 0.40, 95% confidence interval (CI) 0.07 to 2.25; P = 0.30). The meta‐analysis for graft patency comparing ticlopidine versus placebo (three RCTs, 339 participants) favoured ticlopidine (OR 0.45, 95% CI 0.25 to 0.82; P = 0.009). There was insufficient evidence to determine if there was a difference in graft patency in studies comparing fish oil versus placebo (two RCTs, 220 participants; OR 0.24, 95% CI 0.03 to 1.95; P = 0.18); and studies comparing clopidogrel and placebo (two RCTs, 959 participants; OR 0.40, 95% CI 0.13 to 1.19; P = 0.10). Similarly, there was insufficient evidence to determine if there was a difference in graft patency in three studies (306 participants) comparing PRT‐201 versus placebo (OR 0.75, 95% CI 0.42 to 1.32; P = 0.31); in one trial comparing the effect of dipyridamole versus placebo (42 participants; OR 0.46, 95% CI 0.11 to 1.94, P = 0.29) and dipyridamole plus aspirin versus placebo (41 participants; OR 0.64, CI 0.16 to 2.56, P = 0.52); in one trial comparing low‐dose warfarin with placebo (107 participants; OR 1.76, 95% CI 0.78 to 3.99, P = 0.17); and one trial (16 participants) comparing sulphinpyrazone versus placebo (OR 0.43, 95% CI 0.03 to 5.98, P = 0.53). The single trial evaluating warfarin was terminated early because of major bleeding events in the warfarin group. Only two studies published data on the secondary outcome of related interventions (surgical or radiological); there was insufficient evidence to determine if there was a difference in related interventions between placebo and treatment groups. No studies reported on the length of hospital stay and data reporting on complications was limited and varied between studies. AUTHORS' CONCLUSIONS: The meta‐analyses of three studies for ticlopidine (an anti‐platelet treatment), which all used the same dose of treatment but with a short follow‐up of only one month, suggest ticlopidine may have a beneficial effect as an adjuvant treatment to increase the patency of AV fistulae and grafts in the short term. There was insufficient evidence to determine if there was a difference in graft patency between placebo and other treatments such as aspirin, fish oil, clopidogrel, PRT‐201, dipyridamole, dipyridamole plus aspirin, warfarin, and sulphinpyrazone. However, the quality of the evidence was low due to short follow‐up periods, the small number of studies for each comparison, heterogeneity between trials and moderate methodological quality of the studies due to incomplete reporting. It, therefore, appears reasonable to suggest further prospective studies be undertaken to assess the use of these anti‐platelet drugs in renal patients with an arteriovenous fistula or graft.